2014
DOI: 10.1371/journal.pone.0088474
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling Protein 2 and 4 Expression Pattern during Stem Cell Differentiation Provides New Insight into Their Putative Function

Abstract: Apart from the first family member, uncoupling protein 1 (UCP1), the functions of other UCPs (UCP2-UCP5) are still unknown. In analyzing our own results and those previously published by others, we have assumed that UCP's cellular expression pattern coincides with a specific cell metabolism and changes if the latter is altered. To verify this hypothesis, we analyzed the expression of UCP1-5 in mouse embryonic stem cells before and after their differentiation to neurons. We have shown that only UCP2 is present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 56 publications
(75 reference statements)
2
42
1
2
Order By: Relevance
“…UCP4 may be predominantly located in the neuronal cell body (8), where it would dissipate the excessive proton gradient. This location would also better fit UCP4's function in neuronal metabolism (7,27). Indeed, performing two-color dSTORM experiments in the neuronal cell body, we found nearly all mitochondria to be double positive for UCP4/ATP synthase (92.1%) (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…UCP4 may be predominantly located in the neuronal cell body (8), where it would dissipate the excessive proton gradient. This location would also better fit UCP4's function in neuronal metabolism (7,27). Indeed, performing two-color dSTORM experiments in the neuronal cell body, we found nearly all mitochondria to be double positive for UCP4/ATP synthase (92.1%) (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…A recent comparison of wild type and UCP2 -/-or UCP3 -/-knockout mice [21] implied that both proteins are not involved in H + transport. Unfortunately, the tissue(s) chosen in this study were previously shown to have no presence or very low abundance of UCP2/UCP3 under physiological conditions [38,39].…”
Section: Reactive Oxygen Species and Their Derivatives Reactive Aldementioning
confidence: 99%
“…It was previously shown that neuroblastoma cell line N18TG2 expresses UCP2 (22). To determine whether genipin ( Fig.…”
Section: Genipin Does Not Influence Ucp2 Expression But Decreases Thementioning
confidence: 99%
“…One of the possible reasons can be that in many studies, UCP2 is artificially expressed in cells in which it is normally absent. Our group and others have recently shown that UCP2 is confined to rapidly proliferating cells that rely on glycolysis, such as stem cells, activated immunological cells, and cancer cells (22,28,53). The expression of UCP2 in cells that have other metabolic pathways can seriously affect the physiological function of UCP2.…”
Section: Genipin Influenced the Activity Of Membrane Proteins Differementioning
confidence: 99%
See 1 more Smart Citation